Familial coexistence of achalasia and non-achalasic oesophageal dysmotility: evidence for a common pathogenesis. Issue 10 (October 1992) - O'Brien, C J; Smart, H L
Abstract : In five of seven siblings of healthy parents, dysphagia developed during adolescence or early adult life. A barium swallow was normal in one patient but showed appearances considered to be consistent with achalasia in all others. Oesophageal manometry was successfully performed in four of the five patients, including the patient with symptoms but normal radiological appearance. One patient had achalasia, two had oesophageal body motor dysfunction associated with a hypertensive, but normally relaxing lower oesophageal sphincter, and one had diffuse oesophageal spasm alone. The occurrence of three different oesophageal dysmotility disorders within members of a single sibship suggests that these conditions are intimately related and probably genetically determined as an autosomal recessive trait.